Penilaian Risiko dengan Metode HIRADC Pada Pekerjaan Konstruksi Gedung Kebudayaan Sumatera Barat - Taufiq Ihsan; Sarah Azzahra Hamidi; Febyta Amanda Putri (Jurnal Civronlit Unbari, 2020)
Occupational Health and Safety really needs to be a consideration for industry in order to avoid work accidents. Accident prevention can be done by analyzing existing risks, one of which is the HIRADC method, namely identifying hazards (Hazards Identification), assessing risks (Risk Assessment) and controlling risks (Determining Control). This study aims to conduct a risk assessment in the Zone B Phase II project of the West Sumatra Cultural Building. As a managing contractor for the project, PT. X, which is a company in West Sumatra engaged in construction, has tried to prevent work accidents from occurring. However, in the implementation of this project, 12 work accidents were recorded for each of the three types of work, namely ironwork, formwork, and scaffolding. The results of the assessment obtained in the West Sumatra Zone B Phase II Cultural Building construction project have a significant risk. Significant risks need to be considered by contractor management and take corrective action. Recommended improvements are engineering, administrative controls, and use of Personal Protective Equipment.